Analysis of Black Soldier Fly (BSF) Larva as an Effort For Organic Waste Description in Traditional Markets, Jombang Regency - Aisah, Hana Nur; Mika Vernicia Humairo (Universitas STRADA Indonesia, 2022)
The high population density makes people's consumption high, so that the accumulation of waste increases. The waste generated in Jombang Regency is high (417,838 m3/day in 2010). 50% organic waste comes from market waste because traders sell vegetables where vegetables can be sold when they are still fresh, then each vegetable has a different period and some can still be sold for a few days. The purpose of this study was to determine the ability of Black Soldier Fly (BSF) larvae as an effort to decompose organic waste in traditional markets in Jombang Regency. This study uses an experimental quantitative research design. The population is organic waste obtained from traditional markets in Jombang Regency. The sample is organic waste with 8 different treatments and using repetition. The independent variable is the Black Soldier Fly (BSF) larvae, while the dependent variable is the feeding treatment. Data analysis uses the one-way ANOVA test. The results of this study found that there were differences in the speed of decomposition of organic waste using Black Soldier Fly (BSF) larvae and without treatment. Judging from the output of the one-way ANOVA statistical test in the Homogeneous Subsets table, the control column does not have an equation for the speed of decomposition with treatment 1 to treatment 8. There is an effect of feeding on the speed of decomposition of organic waste, with the one-way ANOVA statistical test, a sig value of 0.000 < 0.05.